E-074 Correlation of baseline NLR and CTP imaging in selected patients with large vessel occlusion ischemic stroke. (4th August 2020) - Aly, M; Abdalla, R; Hurley, M; Shaibani, A; Ansari, S
Abstract : Purpose: Many pieces of evidence in the literature suggest that Neutrophils-Lymphocytes ratio (NLR) can be used as an inexpensive biomarker to assess the degree of inflammation for multiple diseases including cancer, coronary artery disease, metabolic syndrome, and sepsis. Cerebral infarction leads to an inflammatory response, ischemic tissue release proinflammatory chemokines which activates leukocytes and enhance their trans-endothelial migration to the site of inflammation. Metanalysis has suggested that baseline NLR is a promising predictor of ischemic stroke clinical outcomes. This study aims to evaluate the relationship between baseline NLR in patients with large vessel occlusion (LVO) and their imaging selection for endovascular treatment (ET). Materials and Methods: We reviewed our prospective stroke intervention database from Nov 2015 to June 2019 for patients that underwent ET for LVO with an admission NLR. Patients were excluded from the study if they received corticosteroids or had any history of infectious/systemic disease prior to the development of stroke symptoms. We studied patient demographics, vascular risk factors, NIHSS on admission, data from imaging (NCCT ASPECT, CTP rCBF <30%, Tmax >6s and mismatch ratio), and 90 days outcome measured by mRS. Statistical analysis was performed with SPSS version 17, univariate analysis was conducted between age, NLR, NIHSS, data from imaging and mRS using a correlation coefficient. Results: Seventy-eight met our inclusion criteria (mean age, 67 ± 19; 39% women, mean NIHSS, 17 ± 6), 95% (n=74) were due to anterior circulation LVO while only 5%(n=4) were due to posterior circulation LVO occlusion. There was a significant positive correlation between NLR and rCBF<30% representing the volume of infarction core (p=0.046), also there was a significant negative correlation between ASPECT score and rCBF<30% (p=0.035). No correlation was observed between NIHSS and ASPECT (p=0.94) or NIHSS and rCBF< 30% (p=0.83), however, there was a trend toward significance correlating NIHSS and Tmax>6s representing the volume of ischemic tissue (p=0.09). Predictably, NLR was not correlating with 90-days mRS (p=0.703) as all patients in our cohort underwent ET, nevertheless, there was a significant correlation between age and 90-days mRS (p=0.001). Conclusions: NLR is an inexpensive and readily available biomarker that correlates with CTP predicted core infarction volume in LVO ischemic stroke. However, in CTP selected patients with relatively small core infarct volumes, NLR may not predict 90-day mRS as endovascular treatment salvages ischemic tissue, minimizes final infarct volume, and suggests follow-up NLR may be more valuable predictor of clinical outcome. Disclosures: M. Aly: None. R. Abdalla: None. M. Hurley: None. A. Shaibani: None. S. Ansari: None.